Mengembangkan skenario panen porang satu musim melalui manipulasi tanam lebih awal dan perlambatan waktu dorman fase generatif dengan pemberian asam salisilat organik alami di lahan kering Lombok Utara - Suparman; Suwardji; Kusnarta; Sukartno (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
The research on the scenario of one-season porang harvest through crop manipulation and delaying dormancy time aims to determine the effect of salicylic acid in breaking the dormancy of porang bulbil seeds during seeding and to determine the effect of slowing down the dormant period of the generative phase, so it is expected to be an alternative porang cultivation technology that is profitable for farmers The method used in this study used a completely randomized design experiment on breaking dormancy and a randomized block design in an experiment with slowing down the dormancy time of the generative phase with four salicylic acid concentrations (0%, 0.5%, 1%, and 2%) with eight replicates were planted under rainfed conditions. The results showed that the concentration of salicylic acid (C7H6O3) 2% was the best treatment in increasing tuber weight (52.25%) compared to the control. Application of Salicylic Acid (2%) was significantly able to increase the vegetative growth of porang plants, which was shown by increasing plant height by 50.38% and breaking seed dormancy 14 days faster than the control (without the addition of Salicylic Acid). Furthermore, the delay in dormancy time occurred 1 month later than the control so that it could prolong the vegetative phase. The concentration of 2% salicylic acid is the best treatment, which can be recommended in the development of one-season porang cultivation technology that can increase farmers' profits.